Divergent response to radio-immunotherapy is defined by intrinsic features of the tumor microenvironment - Christian Klein; Maria Amann; Jacob Gadwa; Laurel B Darragh; Miles Piper; Diemmy Nguyen; Sana D Karam; Michael W Knitz; Justin Yu; Nicholas Olimpo; Sophia Corbo; Jessica I Beynor; et al. (Journal for ImmunoTherapy of Cancer)
Background Treatment with immunotherapy can elicit varying responses across cancer types, and the mechanistic underpinnings that contribute to response vrsus progression remain poorly understood. However, to date there are few preclinical models that accurately represent these disparate disease scenarios.Methods Using combinatorial radio-immunotherapy consisting of PD-1 blockade, IL2Rβγ biased signaling, and OX40 agonism we were able to generate preclinical tumor models with conflicting responses, where head and neck squamous cell carcinoma (HNSCC) models respond and pancreatic ductal adenocarcinoma (PDAC) progresses.Results By modeling these disparate states, we find that regulatory T cells (Tregs) are expanded in PDAC tumors undergoing treatment, constraining tumor reactive CD8 T cell activity. Consequently, the depletion of Tregs restores the therapeutic efficacy of our treatment and abrogates the disparity between models. Moreover, we show that through heterotopic implantations the site of tumor development defines the response to therapy, as implantation of HNSCC tumors into the pancreas resulted in comparable levels of tumor progression.Conclusions This work highlights the complexity of combining immunotherapies within the tumor microenvironment (TME) and further defines the immune and non-immune components of the TME as an intrinsic feature of immune suppression.